Differences in African Banking Systems: Causes and Consequences - Samuel Mutarindwa; Dorothea Schäfer; Andreas Stephan (Global Labor Organization (GLO), 2021)
This paper links banking system development to the colonial and legal history of African countries. Based on a sample of 40 African countries from 2000 to 2018, our empirical findings show a significant dependence of current financial institutions on the inherited legal origin and the colonization type. Findings also reveal that current financial legal institutions are not major determinants of banking system development, and that institutional development and governance quality are more important. A high share of government spending relative to GDP also positively affects banking system development in African countries.
Keywords: G21; G38; G39; K15; K40; 330; Legal origin; colonial history; financial institutions; banking system; correlated random effects model